The influence of investor sentiment on sector indices – the INI index analysis - Rutkowska, Aleksandra (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
In this paper, we examine the influence of investor sentiment on the WSE sector indices. The stock market indices chosen are based on the industry sector, to distinguish the sectors most susceptible and robust to the effects of sentiment. The Polish Investor Sentiment Index (INI) is used as a sentiment measurement. INI is published every week by the Polish Association of Individual Investors based on the opinions of approx. 350 respondents. Individual investors answer the question about their opinion on the stock exchange trend in the next 6 months, whether the trend will be upward, horizontal, or downward. The aim of this study is to understand the impact of investor sentiment on sector indices. The study covers the 5-year period from June 2011 to June 2016. We examine the bivariate relationship in the mean by using the vector autoregression (VAR) model and Granger causality. The results show that INI does not influence the sector indices except for WIG-food and WIG-basic materials. However, the study identifies strong dependencies in the opposite direction
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 227-239
Keywords: investor sentiment; sector indices; VAR; nastrój inwestorów; indeksy sektorowe